#Boycottautismspeaks: communicating a counternarrative through cyberactivism and connective action. Issue 8 (3rd August 2018) - Parsloe, Sarah M.; Holton, Avery E.
ABSTRACT: A growing body of research is examining the role of cyberactivism in facilitating social movements. Yet, few have considered the interplay between cyberactivism and disability advocacy. Through a case study of the #boycottautismspeaks movement, this study finds that cyberactivism may provide platforms for self-advocates to connect through bridging and bonding in unique ways that draw together and give voice to individuals who otherwise may not have means for such dynamic engagement. Drawing on a sample of approximately 10, 000 tweets that circulated with the #boycottautismspeaks hashtag, this research applies thematic analysis and the Social Identity Model of Deindividuation Effects to reveal how counternarratives of disability are developed and circulated via cyberactivism. Findings reveal that #boycottautismspeaks contributors communicated to enhance bonding through (a) (dis)identification, (b) collaboration, and (c) creative resistance. In addition, they communicated to facilitate bridging by (a) demonstrating morality, (b) appealing to humanity, and (c) aligning with other causes. The #boycottautismspeaks movement melded the logic of collective and connective action, provided opportunities for both coordinated and self-directed activity, developing a network of networks through various stitching mechanisms, and cultivating an affective public. Implications for cyberactivism research and practice as well as disability advocacy are discussed.